Pengembangan Teknologi Bahan Mendukung Pembangunan Berkelanjutan Bidang Teknik Sipil (High Volume Fly Ash Self Compacting Concrete/ HVFA-SCC) - Much Suranto; Darupratomo Darupratomo; Hendro Saputro (Jurnal Sipil Terapan, 2024)
The aim of this literature study is to conclude that the use of fly ash as a replacement material for most of the functions of cement in concrete mixes meets the standards for using concrete mixes as environmentally friendly building construction materials in the context of sustainable development, reducing the risk of the greenhouse effect caused by carbon dioxide. The conclusion is that Fly ash, as waste from burning coal for power plants, can be used as a substitute for most of the functions of Portland cement, so that the waste material becomes an economic value and an effort to save the environment. And the mechanism for using HVFA-SCC concrete provides a work productivity solution in the construction sector in reducing the use of labor more efficiently and economically, as well as reducing the use of a large proportion of cement in the concrete composition. Fly ash contains physical and chemical elements with an equivalent composition that is similar to Portland cement. The softness of the fly ash grains is beneficial for filling empty spaces, making the concrete denser and more compact. The equivalent physical and chemical properties mean that fly ash can replace Portland cement.